TITLE: ENHANCING ESL LEARNING WITH KAHOOT: A FUN AND INTERACTIVE CLASSROOM TOOL (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article examines how to improve ESL (English as a Second Language) training in the classroom by utilizing Kahoot, a game-based learning platform. The advantages of Kahoot for encouraging student participation in language learning activities, critical thinking, teamwork, and engagement are covered by the author. Through the use of engaging and interactive games, Kahoot encourages students to engage in language learning, strengthens their vocabulary and grammar, and offers real-time feedback to monitor their progress. The essay emphasizes how Kahoot may help ESL students develop critical thinking abilities, collaborate with others, and create a lively and competitive learning atmosphere. In order to give students a more interesting and productive learning experience, the author generally supports including Kahoot into ESL classes.